LOSSES ON THE ATLANTIC MATA VEGETATION INDUCED BY LAND USE CHANGES - Nascimento Lopes, Elfany Reis do [UNESP]; Abreu Sales, Jomil Costa [UNESP]; Sousa, Jocy Ana Paixao de [UNESP]; Amorim, Amanda Trindade [UNESP]; Albuquerque Filho, Jose Luiz; Lourenco, Roberto Wagner [UNESP] (Univ Federal Lavras-ufla, 2018)
Land use changes are related to urbanization, economics and technology, influencing the management of natural resources and the ecosystem processes. The present study evaluated the behavior of land use changes in the period of 2007 and 2016, and identified the influence of these changes on the Atlantic Forest vegetation and the expected consequences for a future scenario in the short (2020) and medium term (2025). The study was developed in the Una river basin, located in southeastern Brazil. Land use mapping was performed using Landsat 5 and Sentinel-2A satellite imagery, with visual interpretation techniques. The assessment of land use changes and ecological losses was modeled in the Land Change Modeler and the gains and losses for each category and their future scenarios were identified. The calculations of landscape metrics were performed with the V-LATE extension for ArcGIS. The Anthropogenic Exposure Indicator was applied to evaluate the exposure of fragments. The comparative between land uses showed an increase of 484.33 ha of anthropogenic areas and a decrease of 484.14 ha of vegetation. The greater conversion of forests to other uses was related to agriculture. The fragments are under intense edge effect and 13.70% are under high anthropogenic exposure. By 2016, a loss of 484 ha of Atlantic Forest was identified, being expected a loss of 694.11 ha by 2020 and of 934.10 ha by 2025.
Keywords: Fragmentation; Forests; Anthropogenic Exposure; Future Forest Scenarios